Two contrasting approaches to auto-ignition modelling for HCCI engines - Floweday, Gareth (Department of Mechanical Engineering, 2015)
This body of work entailed the broad contrasting of two hydrocarbon fuel auto-ignition models formulated for the emulation of combustion dynamics in Homogeneous Charge Compression Ignition (HCCI) engines. The first (empirical) auto-ignition model was adapted from its previously published form, for HCCI engine model implementation. This model was then combined with an explicit, single zone, thermodynamic engine model in order to investigate combustion phasing control strategies over a wide range of engine design parameters, experimental conditions and hydrocarbon fuels. This investigation yielded new techniques for HCCI combustion phasing control using convergent control parameter values and operation along curves of constant combustion phasing. These techniques were validated experimentally using two HCCI engines of novel design. The second (functional global) auto-ignition model was formulated in this study, drawing on an analysis of chemical kinetic schematics, a detailed auto-ignition behavioural study and a critical evaluation of existing global auto-ignition models. The performance of this new functional global model was evaluated using detailed chemical kinetic simulation data for a variety of hydrocarbon fuels, across a wide range of experimental conditions. The two studies, although different in approach and scope, enabled a broad and detailed comparison of the two auto-ignition models, thereby highlighting their respective values and limitations. The two models were shown to each possess particular advantages in the context of HCCI auto-ignition modelling, which were unmatched by existing models of similar classification. The models were also shown to exhibit individual drawbacks which played to each other's strengths. Both models were shown to be configurable to real world, full boiling range fuels and were designed to accurately emulate the dynamics of two-stage auto-ignition with excellent computational efficiency. These two hydrocarbon fuel auto-ignition models, together with the engine modelling techniques developed in this study, represent a novel and valuable contribution to the field of HCCI engine combustion control and effectively move this technology one incremental step closer to its anticipated commercial realisation.